Strengthening Entrepreneurship Literacy as a Strategy for Enhancing Community-Based Local Economic Potential: A Case Study in Denai VillageBird's Nest - Dalimunthe, Ritha F; Nauly, Meutia; Selamat, Nor Hafizah; Fadli, Fadli; Ramadani, Ramadani; Siregar, M. Bangun; Adelia, Nurul; Supriadi, Supriadi (Asian Journal of Management Analytics, 2025)
This case study examines the strengthening of entrepreneurial literacy as a strategy to increase the potential of community-based local economies in Denai Sarang Burung Village. Through training, mentoring, and international collaboration, female MSME actors have succeeded in increasing managerial capacity, digital marketing, and product innovation. The establishment of institutions such as the Red and White Cooperative and the Joint Business Group strengthens business networks and business sustainability. The challenge of women's dual roles and aspects of business legality are the focus of the development of advanced programs. This study recommends ongoing mentoring, practice-based training, and scientific publications as efforts to disseminate and develop academics.